Keanekaragaman Spesies Kupu-kupu (Lepidoptera) pada Habitat Ekowisata Kawasan Hutan Desa Tahawa Kabupaten Pulang Pisau - Fandi Tuju (Journal of Biotropical Research and Nature Technology, 2023)
Butterflies are part of biodiversity that is important to be preserved because the presence of butterflies in an ecosystem, especially forests, is very important, both as part of the food chain, pollinators, and food for other animals. This study aims to analyze the species diversity and abundance of butterflies (Lepidoptera) in the habitat of Tahawa Village Forest Area, Pulang Pisau Regency. The research method used an exploratory survey method with a sweeping technique following a transect line and then calculated Shannon-Wiener Diversity Index (H'), Evenness Index (E), and Species Richness Index (R1). Butterflies found in the Tahawa Village Forest Area consisted of 6 families divided into 15 species with a total of 63 individuals. The most species found came from the Pieridae family and the least from the Geometridae family. The Diversity Index (H') obtained a value of 2.38, classified as moderate diversity. The Evenness Index (E) is in the high category with 0.88, while the Richness Index (R1) is at 3.38 which is still classified as low.